Spatial analysis of residential land prices in Jeddah city - Alsharif, Shaker Abdullah (Arab Journal for Sciences and Research Publishing, 2023)
This study is concerned with identifying the average residential land prices in Jeddah city and understanding the most important spatial factors that affect them. The study found a discrepancy in the average residential land prices per square meter. Prices were high in the city center and very high in some sub- municipalities. The northwestern direction and decreases in the southern and eastern direction. The spatial factors affecting the average prices of residential lands in the sub- municipalities of Jeddah were identified. The most important factors were the availability of public services, infrastructure services, and population density, followed by the factor of proximity to the city center and the waterfront, and finally the type of planning. Prices also rise. On the main axes: King Abdulaziz Road, Medina Road, and Hira Street.
Keywords: Spatial analysis; Residential land prices; Jeddah City